Zinc Uptake, Translocation, and Remobilization in Winter Wheat as Affected by Soil Application of Zn Fertilizer - Liu, Dun-Yi; Liu, Yu-Min; Zhang, Wei; Chen, Xin-Ping; Zou, Chun-Qin (Frontiers in Plant Science, 2019)
Effect of zinc (Zn) application to soil on root growth and Zn uptake and translocation in winter wheat are poorly understood. This study evaluated the effect of soil Zn fertilization (0, 2.3, 5.7, 11.4, 22.7, 34.1 kg of Zn ha-1) on root growth and distribution, crop Zn uptake, root-to-shoot translocation of Zn, and remobilization of Zn from shoot to grains. Results of this study revealed that Zn application < 11.4 kg ha-1 significantly increased root dry weight, root length density, and root surface area within 0-30 cm soil depth and higher rates of Zn application caused slight decreases in these root parameters. Shoot biomass and shoot Zn accumulation increased as Zn application rate increased mainly because of improved matching of root growth and enhanced availability of Zn in the topsoil layer. Post-anthesis Zn uptake by shoot increased and translocation of Zn from root to shoot decreased as rate of Zn application increased. The degree to which Zn accumulation in grains resulted from pre-anthesis remobilization vs. post-anthesis shoot uptake depended on Zn availability in soil; post-anthesis shoot uptake dominated at DTPA-Zn concentrations > 7.15 mg kg-1, and pre-anthesis remobilization dominated at lower soil Zn levels. In conclusion, Zn uptake, translocation and remobilization to grain were affected by root growth and its matching with the availability of soil Zn. The results suggest that soils similar to the study soil should be fertilized to 30 cm depth with about 11.4 kg ha-1 Zn in order to obtain high yield and grain Zn concentration of wheat.